Analisis Mobilitas Sirkuler Pedagang Kaki Lima Di Kecamatan Kartasura - M, Ramlah, Drs. Priyono, M.Si (2017)
This research entitled as "Circular Mobility Analysis of Street Vendors in Kartasura Sub-District". This research aims to review of social demography characteristic of Street Vendors: (1) (Age, Sex, Educations), (2) Reason of choosing as a street vendor, (3) Motivating factor to do circular mobility in Kartasura Sub-District. The method used in this research is Survey Method. The sample collected by 35% (37 respondents) of 110 populations with using a questionnaire. System of determining respondent by Random Sampling which: taking sample each sub population equally. The most center of activity of street vendors are at: curb of UMS, bus station, traditional market of Kartasura, Gumpang market. Data collected by primary and secondary data. The result of this research is: (1) the age of street vendors are productive which average to 41 years, the "sex" of street vendors mostly men by 22 persons (59.46%), from 37 respondents, the education level of street vendors that are passed generally from Elementary School and Junior High School (SD and SLTP), SD by 12 persons (32.43%); SLTP by 12 persons (32.43%); (2) the reason of choosing job as street vendor generally caused by "no other jobs" by 19 persons (51.53%) of 37 respondents. (3) the affecting factors primarily caused by economic by 17 persons (45.95%). According to result of calculation it was affected by location, goods, and working time. The income mostly ranged by Rp.5000000- Rp. 8000000/months. This income generally had from the type of goods of trading by clothes and fruits. The lowest income by Rp. 3000000/months of street vendors are trading foods and beverages. Keywords: Mobility, Street Vendors, Distribution.